Menggali Nilai-Nilai Moderasi Beragama Pada Tradisi Doa Makam di Desa Tarokan Kidul - syakdiyah, Halimatus syakdiyah; Maghfiroh, Linda; Billah, Zahida I’tisoma (Kalam Nusantara Institute, 2024)
Abstract The tradition of tahlil together at the grave in Tarokan Kidul village is a tradition that has been passed down from generation to generation and is also a religious system as a sense of caring for the grave's master. This tradition is unique in the village of Tarokan Kidul, where in this activity there is the reading of tahlil, yasin together as well as tausiah, which is held every Thursday afternoon in the pavilion right in the middle of the grave. The aim of this community service activity is to find out the form of tradition, function and meaning of the tradition of joint grave prayer in Tarokan Kidul village. The approach used in this community service activity is the ABCD approach, where there is a stage in carrying out this approach, namely the inculturation stage where, in this stage the researcher mixes with the surrounding community, namely by carrying out congregational prayers at the mosque, teaching at school, posyandu activities, and carrying out other traditional community activities, the second stage is area tracing, namely the researcher explores rural areas of KKN locations such as rivers, rice fields, which produces images in the form of transects, the third stage is asset mapping, namely collecting data on assets owned by local village communities, here the researcher goes around to small businesses and researchers discovered cultural assets, namely the tradition of praying together at graves, the next stage was choosing a priority scale and appreciative discovery, namely cultural assets in the form of praying together with village residents at graves, the final stage was the define and reflection stage, namely there were forms, functions, and meaning in the shared tahlil tradition. This form of tradition is a series of processions, traditions and rituals. The procession includes cleaning, tahlil, yasin, recitation. This tradition has a function for society as a social function, religious function, educational function, preserving culture. The result of this community service activity is that there is an element of religious moderation in the tradition of joint grave prayer, namely respecting differences in beliefs, increasing understanding of tolerance, practicing religious values, creating dialogue of beliefs, and avoiding conflicts with community traditions.